Story revolutions : collective narratives from the Enlightenment to the digital age - Lénárt-Cheng, Helga (Cultural frames, framing culture., 2022)
"This book examines the power of autobiographical stories, when aggregated in large numbers, to fuel social and political movements by shaping people's sense of community"--